2019
DOI: 10.3390/batteries5010024
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxygen Fuel Cell Utilising High Concentration Electrolyte

Abstract: A vanadium oxygen fuel cell is a modified form of a conventional vanadium redox flow battery (VRFB) where the positive electrolyte (VO2+/VO2+ couple) is replaced by the oxygen reduction (ORR) process. This potentially allows for a significant improvement in energy density and has the added benefit of overcoming the solubility limits of V (V) at elevated temperatures, while also allowing the vanadium negative electrolyte concentration to increase above 3 M. In this paper, a vanadium oxygen fuel cell with vanadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The utilization of air as one of the electrolytes removes the need to use two tanks to store energy but also unlocks the potential to increase the concentration of vanadium in the electrolyte operating at higher temperatures, since the V (V) solubility problems do not influence this technology. In 2019, a VAFC was reported by Risbud et al [234]. They achieved a power density of 22 mW cm −2 at 40 mA cm −2 with a vanadium concentration of 3.6 M. With this concentration of vanadium, the VAFC has a theoretical energy density of 143.8 Wh L −1 , almost 3.5 times greater than a VRFC with the same concentration of active species.…”
Section: Metal-air Flow Batteries (Mafb) and Metal-air Fuel Cells (Mafc)mentioning
confidence: 98%
“…The utilization of air as one of the electrolytes removes the need to use two tanks to store energy but also unlocks the potential to increase the concentration of vanadium in the electrolyte operating at higher temperatures, since the V (V) solubility problems do not influence this technology. In 2019, a VAFC was reported by Risbud et al [234]. They achieved a power density of 22 mW cm −2 at 40 mA cm −2 with a vanadium concentration of 3.6 M. With this concentration of vanadium, the VAFC has a theoretical energy density of 143.8 Wh L −1 , almost 3.5 times greater than a VRFC with the same concentration of active species.…”
Section: Metal-air Flow Batteries (Mafb) and Metal-air Fuel Cells (Mafc)mentioning
confidence: 98%
“…Zhu et al [148] reported a novel battery design utilizing a nanostructured lithium manganese oxide cathode and a hydrogen gas anode in an aqueous electrolyte. A vanadium-oxygen RFB used a 3.6 M V 2+/3+ ion concentration at the anode and H 2 O/O 2 redox reaction at the cathode generating an overall OCV of 1.49 V [149].…”
Section: Hybrid Reactants In Eesmentioning
confidence: 99%
“…The overall standard cell potential is 1.26 V at 25 o C, but for a cell comprising an electrolyte composition of 2 M vanadium in 5 M sulphuric acid, the open-circuit potentials is 1.4 and 1.6 V at 50% and 100% state of charge (SOC) respectively. 97…”
Section: Cell Reactionsmentioning
confidence: 99%
“…[88][89][90][91][92][93] • V O −1 redox fuel cell. [94][95][96][97] This paper presents some of the highlights of the UNSW All-Vanadium Redox Flow Cell R&D program.…”
mentioning
confidence: 99%